Pravice oseb LGBT+ v slovenski upravni praksi - Košec, Klavdija (Javna uprava, 2023)
Democratic societies are largely characterized by their respect for human rights, particularly for vulnerable groups such as the LGBT+ community. This article, therefore, explores the regulations and theoretical grounds for the protection of these individuals, with a focus on administrative procedures, which are most commonly employed in asserting their legal position. The aim of this analysis is to identify instances of administrative violations in Slovenia to improve the situation in the future. The research utilized several methods, including a review of Slovenian Ombudsperson annual reports and case studies, as well as structured interviews with, for example, representatives of LGBT+ individuals from the NGO Legebitra. In the discussion section, the authors argue that although procedural legal regulation is adequate, reported violations are infrequent. This is not necessarily indicative of societal openness and awareness of needs but may be attributed to the (still) low level of enforcement of legal protections.
Keywords: administrative procedures; človekove pravice; human rights protection; LGBT+; ombudsman; upravni postopki; upravno pravo; ustavno pravo; Varuh človekovih pravic